CREATIVELY NEGOTIATING THE PLACE OF SPIRITUALITY IN THE ELT CURRICULUM - Mambu, Joseph Ernest (TEFLIN Journal, 2017)
This article aims to better understand constraints (e.g., hostility toward spirituality) and opportunities that may affect teacher-student and student-student relations as spiritually informed ELT curriculum is negotiated. Viewed more broadly, spirituality aims to foster the ability to see one's own religious positioning in relation to other people who have different faiths, and the commitment to being connected with other people, as well as nature, with love. In terms of pedagogical methodology, negotiating the place of spirituality in ELT means creatively keeping the balance of mainstreaming and decentering different senses of spirituality. It is in line with Kumaravadivelu's theoretical lens of postmethod pedagogy which sheds light on how a teacher theorized negotiating power relations associated with his spirituality; how a teacher exploited a religious issue unique to a specific context in Indonesia; and how the dialogue of religious issues can be extended beyond what already happened in class. Regarding spiritually informed materials development, this article focuses on teacher-student co-development of spiritually informed materials and adaptations of non-ELT materials. The article concludes with some pedagogical implications and major questions to be addressed in future research on spiritually informed ELT curriculum.